LEGAL EFFORTS OF TAX MANDATORY OBJECTIVES ON TAX PROVISIONS (Study in the Regional Office of General Directorate of Taxation of South Jakarta I) - Sumbaga, Andri Prasetyo; Halim, Paisal; Badruddin, Syamsiah; Bombang, Saifullah; Djanggih, Hardianto (Yustisia, 2018)
The focus of this study is on the resolution of objections raised by Taxpayers in the Regional Office of DGT South Jakarta I. The theory used in this study refers to the opinion of Adam Smith in his book Wealth of Nations which states that a good tax collection must fulfill equity and equality requirements, certainty , convenience of payment, and efficiency. This study uses a naturalistic and interpretive qualitative approach that focuses on the process of resolving taxpayers' objections to a tax assessment as a legal effort. Data collection is done through interviews and direct observation on the object of research. The results of interviews and observations prove that the resolution of the objections to the South Jakarta I DGT Regional Office has been carried out in accordance with the provisions of the applicable tax regulations. This was also reinforced by statements made by Taxpayers who filed objections to the Regional Office of DGT South Jakarta I. The settlement of objections was also carried out to fulfill the rights and justice of the Taxpayers even though the decisions issued differed from the wishes of the Taxpayer. Settlement of objections seen from the rhythm of the work is considered effective, but when viewed from the time of completion, there are several applications that can be completed near the deadline. This is due to the large number of application files for reduction or elimination of administrative sanctions that enter, thus affecting the time to settle complaints.